AB0658 Cross-Cultural Adaptation, Reliability, and Validity of the Turkish Version of the Compliance Questionnaire on Rheumatology (CQR-T) in Patients with Behçet's Disease. (9th June 2015) - Cinar, F.I.; Cinar, M.; Yilmaz, S.; Acikel, C.; Erdem, H.; Pay, S.; Simsek, I.
Abstract : Background: Compliance to treatment can be defined as the degree to which patient behavior is consistent with the recommendations made by healthcare providers. Determining the level of the patient's compliance will improve the management of a certain disease. Currently, the only self-reported questionnaire for assessing the compliance of patients with rheumatic disease is the 19-item Compliance Questionnaire on Rheumatology (CQR). Objectives: The aim of this study was to examine the psychometric properties of the Turkish version of the Compliance Questionnaire on Rheumatology (CQR-T) for patients with Behçet's disease (BD) Methods: A sample of 105 Turkish patients with BD participated in this study. The scale was cross-culturally adapted through a process including translation, comparison with versions in other languages, back translation, and pretesting. Construct validity was evaluated by factor analysis, and criterion validity was evaluated using the Morisky Medication Adherence Scale (MMAS). Results: The mean age of the study group was 30.87±8.06 years. The majority of the participants was male (89.5%). Mean disease duration was 5.67±4.68 years.Among the current medical treatment agents, colchicine and azathioprine were the most commonly used (79 and 50 patients, respectively). The CQR-T demonstrated acceptable internal consistency (Cronbach's alpha coefficient = 0.832), adequate test–retest reliability (intraclass correlation coefficient = 0.630), and correlations with MMAS scores (r=−0.389; p<0.001), indicating convergent validity. Conclusions: The CQR-T was found to be a valid and reliable instrument for evaluating the compliance of Turkish BD patients with prescribed medications. The CQR-T might be a helpful tool in two ways: for determining the level of compliance of patients with BD and for adjusting their management and follow-up based on the results. References: de Klerk, E., van der Heijde, D., Landewé, R., van der Tempel, H., & van der Linden, S. (2003). The compliance-questionnaire-rheumatology compared with electronic medication event monitoring: a validation study. The Journal of Rheumatology, 30, 2469-2475. de Klerk, E., van der Heijde, D., van der Tempel, H., & van der Linden, S. (1999). Development of a questionnaire to investigate patient compliance with antirheumatic drug therapy. The Journal of Rheumatology, 26, 2635–2641. Fialko, L., Garety, P.A., Kuipers, E., Dunn, G., Bebbington, P.E., Fowler, D., & Freeman, D. (2008). A large-scale validation study of the Medication Adherence Rating Scale (MARS). Schizophrenia Research, 100, 53-59. Disclosure of Interest: None declared